Actualization of Character Education in PAI Learning in Elementary School - Burhanul Muttaqin (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Character education is very important because currently there are many students who cannot practice character in their daily lives. The aim of the research carried out by the author is to provide an important overview of the character cultivation that students must have by means of teachers and parents who must work together to always remind students wherever they are to apply character in everyday life. This type of research is qualitative research with the subject of research being Islamic teachers as the main topic of discussion. This is because Islamic teachers are teachers who can require their students to implement character education. Then data collection techniques use interviews and observation. The results of this research explain that character education implemented in the independent curriculum education unit has been determined. So teachers of Islamic Religious Education and Character Education subjects must provide a form of character education in PAI lessons to achieve success in the learning process. These forms are discipline, devotion, honesty, self-awareness, responsibility and empathy.